2011
DOI: 10.1111/j.1440-169x.2011.01254.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of c‐Jun N‐terminal kinase activation in blastema formation during planarian regeneration

Abstract: The robust regenerative abilities of planarians absolutely depend on a unique population of pluripotent stem cells called neoblasts, which are the only mitotic somatic cells in adult planarians and are responsible for blastema formation after amputation. Little is known about the molecular mechanisms that drive blastema formation during planarian regeneration. Here we found that treatment with the c-Jun N-terminal kinase (JNK) inhibitor SP600125 blocked the entry of neoblasts into the M-phase of the cell cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 47 publications
(83 reference statements)
1
62
0
Order By: Relevance
“…In previous studies, PiwiA protein has been found to be expressed, not only in stem cells which are expressing piwiA mRNA, but also in post-mitotic progeny: the stem cell-derived cells (Guo et al, 2006;Yoshida-Kashikawa et al, 2007;Scimone et al, 2010). The blastema cells are almost all post-mitotic cells, as indicated by the absence of mitotic cell markers (Salvetti et al, 2000;Eisenhoffer et al, 2008;Tasaki et al, 2011a;Tasaki et al, 2011b). Therefore, the DjPiwiA protein-expressing cells in the blastema are most likely to be stem cell-derived cells.…”
Section: Islet Functions In the Wnt-expressing Cells Of Planarianmentioning
confidence: 99%
“…In previous studies, PiwiA protein has been found to be expressed, not only in stem cells which are expressing piwiA mRNA, but also in post-mitotic progeny: the stem cell-derived cells (Guo et al, 2006;Yoshida-Kashikawa et al, 2007;Scimone et al, 2010). The blastema cells are almost all post-mitotic cells, as indicated by the absence of mitotic cell markers (Salvetti et al, 2000;Eisenhoffer et al, 2008;Tasaki et al, 2011a;Tasaki et al, 2011b). Therefore, the DjPiwiA protein-expressing cells in the blastema are most likely to be stem cell-derived cells.…”
Section: Islet Functions In the Wnt-expressing Cells Of Planarianmentioning
confidence: 99%
“…The cells that participate in blastema formation already exist from the proliferative state, and a portion of these cells start to form the brain rudiment [25,26]. Therefore, the commitment of DA neurons may immediately occur after brain rudiment and brain pattern formation.…”
Section: Stem Cell Utilization In Vivo and In Vitro For Non-regeneratmentioning
confidence: 99%
“…Subsequently, a blastema (a mass of cells derived from pluripotent stem cells) is formed by mitogen-activated protein (MAP) kinase activation 24 hours after amputation [25,26]. It has been revealed that blastema cells are supplied from the post-blastema region via mitosis from G2-phase pluripotent stem cells.…”
Section: The Early Stage Of Brain Regeneration After Amputationmentioning
confidence: 99%
“…It has also been shown that the Scribble (Scrib) complex, an important determinant of apicobasal polarity, contributes to epithelial cell migration and fusion during both development and wound healing in mammals by recruiting the small GTPases Cdc42, Rac and the serinethreonine kinase Pak to the leading edge (LE) of migrating cells (Murdoch et al, 2003;Zarbalis et al, 2004;Humbert et al, 2006;Dow et al, 2007;Bahri et al, 2010). JNK signaling is required for regeneration after wounding in zebrafish (Kawakami, 2010, for review), and it plays a crucial role in the differentiation of blastema neoblasts by regulating the G2/ M cell cycle transition during planarian regeneration (Tasaki et al, 2011). Finally, it was shown that expression of Wnt target genes was stimulated by JNK activation, accelerating tumorigenesis (Sancho et al, 2009).…”
Section: Signaling Pathways and Epigenetic Factors Involved In Vertebmentioning
confidence: 99%